Transforming Teacher Competence through ChatGPT: Designing Innovative and Effective Lesson Modules - Istiarsyah Istiarsyah; Maisura Maisura; Nurhabibah Nurhabibah; Kumita Kumita; Kamarullah Kamarullah (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
This study investigates the potential of ChatGPT, an Artificial Intelligence (AI), to transform teacher competence and lesson design in a junior high school setting in Lhokseumawe, Indonesia. A quasi-experimental pre-test and post-test design was employed with 25 junior high school teachers from Ihyaaussunnah, Lhokseumawe, Aceh. These teachers were asked to utilize ChatGPT for various pedagogical tasks, including lesson planning, assessment design, and content creation. Pre- and post-test questionnaires assessed changes in teacher competence, while a rubric was used to evaluate the quality of lesson modules designed with ChatGPT. Results revealed significant improvements in all measured aspects of teacher competence, including pedagogical knowledge, technological proficiency, and confidence in using ChatGPT for instructional purposes. Lesson modules created with ChatGPT were rated highly across all evaluation criteria, indicating their effectiveness and alignment with modern pedagogical approaches. Qualitative feedback from teachers highlighted the time-saving benefits of ChatGPT, its ability to enhance creativity and personalize learning experiences, and its potential to spark new pedagogical approaches. However, some teachers reported initial challenges in formulating effective prompts and emphasized the need for ongoing support and training. This study provides valuable insights into the potential of ChatGPT to empower teachers and improve instructional design. However, the small sample size and context-specific nature of the findings limit generalizability. Further research is needed to explore the long-term impact of ChatGPT on teacher competence and student learning outcomes in diverse educational settings.